TESTING OF MICROPROCESSOR DEVICES ON THE BASIS OF ARTIFICIAL NEURAL NETWORKS WITH CHANGEABLE PARAMETERS - Lokazyuk, Viktor; Cheshun, Viktor; Chornenkiy, Vitaliy (International Journal of Computing, 2014)
The base principles of a technique of application of 3-layer feedforward fullconnected artificial neural network for execution of adaptive algorithms of testing of digital microprocessor devices are considered. The method of change of weight coefficients and thresholds of artificial neurons in the mode of operation of artificial neural network realized at the hardware level is considered. The application of this method provides implementation of adaptive algorithms of testing of the large complexity with the limited hardware resources of artificial neural network.